2012
DOI: 10.2478/v10018-012-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

GNSS Receiver Zero Baseline Test Using GPS Signal Generator

Abstract: Validation of the performance of GPS receivers is crucial for many applications. This paper presents testing GPS receivers with the use of a GPS signal simulator. Unlike live testing, testing with simulators provides full control of simulated satellite signals and simulation environmental conditions. Moreover, generating repeatable signals makes possible to extend typical procedures. It allows to determine the absolute value of the position precision for each receiver without relation to any other one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Hence, the GPS/GNSS zero‐baseline time series vary around zero, expressing the impact of the errors due to the geometry of the satellite constellation, amplified by the receiver noise 35 . The zero‐baseline measurements are an approach which has been adopted in many studies for the modelling of the GPS receivers noise and the impact of the satellite constellation 37,38 . In our study, the GNSS base station, apart from reference station for the GNSS stations deployed on the bridge, was also connected to a second GNSS receiver to carry out the zero‐baseline measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the GPS/GNSS zero‐baseline time series vary around zero, expressing the impact of the errors due to the geometry of the satellite constellation, amplified by the receiver noise 35 . The zero‐baseline measurements are an approach which has been adopted in many studies for the modelling of the GPS receivers noise and the impact of the satellite constellation 37,38 . In our study, the GNSS base station, apart from reference station for the GNSS stations deployed on the bridge, was also connected to a second GNSS receiver to carry out the zero‐baseline measurements.…”
Section: Methodsmentioning
confidence: 99%
“…35 The zero-baseline measurements are an approach which has been adopted in many studies for the modelling of the GPS receivers noise and the impact of the satellite constellation. 37,38 In our study, the GNSS base station, apart from reference station for the GNSS stations deployed on the bridge, was also connected to a second GNSS receiver to carry out the zerobaseline measurements.…”
mentioning
confidence: 99%
“…ionosphere and troposphere effects) and multipath [22,23]. Thus, the remaining error of the GNSS solution is due to the geometry of the satellite constellations and the noise of the GNSS receiver [24]. Furthermore, potential impact of BeiDou inter-satellite-type biases (ISTBs) between different types of BeiDou satellites occurs in case of using different GNSS receivers, affecting also the ambiguity resolution of the GNSS records process [25], which is not though the case of our measurements since, similar receivers are used for each pair of receivers.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation was done with the zero baseline test and also with a short baseline test, where for the latter, harmonic functions were used to compensate for the multipath error. In the case of Dróżdż and Szpunar [ 30 ], the noise of observations was determined with a signal simulator, and the results indicated that the quality of observations may vary among different receiver types. The study by Han et al [ 31 ] used an signal-to-noise-dependent environmental model, where observation weights are determined based on the satellite elevation angle in order to reduce the noise in harsh environments.…”
Section: Introductionmentioning
confidence: 99%